2016
DOI: 10.18863/pgy.238190
|View full text |Cite
|
Sign up to set email alerts
|

Yeni Bir Nöropsikolojik Kavram Olarak Tamamlanma İhtiyacı

Abstract: ÖzBilişsel tamamlanma ihtiyacı, son zamanlarda davranışsal nörobilimin önem kazanmaya başlayan konularından biridir ve bireyin belirli bir konuda karmaşa ve belirsizlik yerine kesin bir bilgiye ulaşma ihtiyacı, karar verme arzusu olarak tanımlanabilir. Bu çalışmada tamamlanma ihtiyacı kavramı, kısa bir gözden geçirme ile kuramsal ve görgül çalışmalar bağlamında detaylı olarak ele alınmıştır. Ayrıca, bu yazıda tamamlanma ihtiyacı ile ruh sağlığı ilişkisi de ele alınmıştır. Literatürde, tamamlanma ihtiyacı konus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Many studies have supported the fact that intolerance of uncertainty triggers anxiety (Buhr & Dugas, 2009;2012;Carleton, Collimore, Asmundson, 2010;Carleton et al, 2012;Carleton, Norton& Asmundson, 2007;Carleton, Sharpe & Asmundson, 2007). Consequently, the findings of the study are of a nature that supports the finding of the research, and it is a probable case that intolerance of uncertainty, which is itself a negative structure (Atak, Syed, Cok & Tonga, 2016), brings about negative sentiments, such as anxiety, depression, unhappiness, with a higher incidence in families with disabled children. Therefore, the first hypothesis of this research has been confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…Many studies have supported the fact that intolerance of uncertainty triggers anxiety (Buhr & Dugas, 2009;2012;Carleton, Collimore, Asmundson, 2010;Carleton et al, 2012;Carleton, Norton& Asmundson, 2007;Carleton, Sharpe & Asmundson, 2007). Consequently, the findings of the study are of a nature that supports the finding of the research, and it is a probable case that intolerance of uncertainty, which is itself a negative structure (Atak, Syed, Cok & Tonga, 2016), brings about negative sentiments, such as anxiety, depression, unhappiness, with a higher incidence in families with disabled children. Therefore, the first hypothesis of this research has been confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…Gizem Erdem https://orcid.org/0000-0003-3507-1290 ENDNOTES 1 In their construct validity study, Atak and Çok (2010) found that emerging adulthood is a developmental phase for urban and unmarried youth in Turkey, in contrast to rural youth, who usually marry younger. Therefore, we only recruited urban youth to the current study.…”
Section: Orcidmentioning
confidence: 99%
“…The second is the tendency to maintain closure or completion or to ensure continuity by freezing. This freezing tendency continues to use old and acquired knowledge to eliminate new and contradictory information (Atak, 2016). Every uncertain, uncanny, confusing and confusing external incident will push individuals to search for solutions.…”
Section: Norms and Information That Change With Disastersmentioning
confidence: 99%